What Does the Sleeping Brain Say? Syntax and Semantics of Sleep Talking in Healthy Subjects and in Parasomnia Patients - Arnulf, Isabelle; Uguccioni, Ginevra; Gay, Frederick; Baldayrou, Etienne; Golmard, Jean-Louis; Gayraud, Frederique; Devevey, Alain (Sleep (New York, N.Y.), 2017)
Speech is a complex function in humans, but the linguistic characteristics of sleep talking are unknown. We analyzed sleep-associated speech in adults, mostly (92%) during parasomnias. The utterances recorded during night-time video-polysomnography were analyzed for number of words, propositions and speech episodes, frequency, gaps and pauses (denoting turn-taking in the conversation), lemmatization, verbosity, negative/imperative/interrogative tone, first/second person, politeness, and abuse. Two hundred thirty-two subjects (aged 49.5 ± 20 years old; 41% women; 129 with rapid eye movement [REM] sleep behavior disorder and 87 with sleepwalking/sleep terrors, 15 healthy subjects, and 1 patient with sleep apnea speaking in non-REM sleep) uttered 883 speech episodes, containing 59% nonverbal utterance (mumbles, shouts, whispers, and laughs) and 3349 understandable words. The most frequent word was "No": negations represented 21.4% of clauses (more in non-REM sleep). Interrogations were found in 26% of speech episodes (more in non-REM sleep), and subordinate clauses were found in 12.9% of speech episodes. As many as 9.7% of clauses contained profanities (more in non-REM sleep). Verbal abuse lasted longer in REM sleep and was mostly directed toward insulting or condemning someone, whereas swearing predominated in non-REM sleep. Men sleep-talked more than women and used a higher proportion of profanities. Apparent turn-taking in the conversation respected the usual language gaps. Sleep talking parallels awake talking for syntax, semantics, and turn-taking in conversation, suggesting that the sleeping brain can function at a high level. Language during sleep is mostly a familiar, tensed conversation with inaudible others, suggestive of conflicts.